2017
DOI: 10.2147/jpr.s139387
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine in perioperative acute pain management: a non-opioid adjuvant analgesic

Abstract: Many nociceptive, inflammatory, and neuropathic pathways contribute to perioperative pain. Although opioids have long been a mainstay for perioperative analgesia, other non-opioid therapies, and dexmedetomidine, in particular, have been increasingly used as part of a multimodal analgesic regimen to provide improved pain control while minimizing opioid-related side effects. This article reviews the evidence supporting the preoperative, intraoperative, and postoperative efficacy of dexmedetomidine as an adjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 46 publications
1
69
0
5
Order By: Relevance
“…Moreover, Dex has been proved to alleviate NPP by modulating the Janus kinase (JAK)–signal transducer and activator of transcription (STAT) pathway in rats (Xun & Zheng, 2020), indicating its association with sensory abnormalities. A wide spectrum of clinical studies have demonstrated that intraoperative Dex significantly reduced postoperative pain intensity and the need for opioid application, and the incidence of opioid‐associated adverse events (Schnabel, Meyer‐Friessem, Reichl, Zahn, & Pogatzki‐Zahn, 2013; Tang & Xia, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Dex has been proved to alleviate NPP by modulating the Janus kinase (JAK)–signal transducer and activator of transcription (STAT) pathway in rats (Xun & Zheng, 2020), indicating its association with sensory abnormalities. A wide spectrum of clinical studies have demonstrated that intraoperative Dex significantly reduced postoperative pain intensity and the need for opioid application, and the incidence of opioid‐associated adverse events (Schnabel, Meyer‐Friessem, Reichl, Zahn, & Pogatzki‐Zahn, 2013; Tang & Xia, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Different pathways between the sedation and analgesic effects of dexmedetomidine could explain it perhaps (16). The effect of dexmedetomidine is mediated by the ascending noradrenergic pathway in the locus coeruleus, while the analgesic effect occurs via an a2-adrenergic receptor-dependent descending pathway in the spinal cord (20). Animal studies have shown that the addition of dexmedetomidine to local anesthetic would increase the duration of sensory and motor blockade in a rat model of sciatic nerve blockade (21).…”
Section: Discussionmentioning
confidence: 99%
“…A escolha cuidadosa e individualizada do protocolo anestésico deve ser sempre prioridade, sobretudo para mamíferos exóticos, cujas particularidades fisiológicas requerem práticas pormenorizadas de contenção em detrimento dos riscos para o paciente e para a equipe [1]. A dexmedetomidina é um sedativo alfa-2 agonista que foi eleito em razão da elevada seletividade; ação relaxante muscular; possibilidade de administração por vias alternativas à intravenosa; menor interferência na função respiratória em relação a outros medicamentos da classe; oferta analgésica adicional, além de possuir antagonista específico [7,13].…”
Section: Discussionunclassified